Monotonicity and robustness in Wiener disorder detection - Ekström, Erik; Vaicenavicius, Juozas (Sequential analysis, 2019)
We study the problem of detecting a drift change of a Brownian motion under various extensions of the classical case. Specifically, we consider the case of a random post-change drift and examine monotonicity properties of the solution with respect to different model parameters. Moreover, robustness properties - effects of misspecification of the underlying model - are explored.